Model-based event-triggered control with time-varying network delays - Garcia, E.; Antsaklis, P. J. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
In this paper two approaches for reducing communication traffic in a control network, namely, Model-Based Networked Control Systems (MB-NCS) and event-triggered control, are unified under a single framework. The use of a model of the plant in the controller node not only generalizes the Zero-Order-Hold (ZOH) implementation in traditional event-triggered control schemes but it also provides stability thresholds that are robust to model uncertainties. With respect to MB-NCS, the stability conditions presented here do not need explicit knowledge of the plant parameters as in previous work but are given only in terms of the parameters of the nominal model and some bounds in the model uncertainties. The resulting framework is capable of increasing the update time intervals compared with the individual approaches considered in this paper.